2018
DOI: 10.1108/ebr-04-2017-0076
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of risk reporting by Portuguese and Spanish non-finance companies

Abstract: Purpose-The paper seeks to assess the risk reporting practices across two European Latin countries (Portugal and Spain). Moreover, drawn on elements of agency, legitimacy, resources-based perspectives, and institutional theory this study also intends to assess if the influence of corporate governance mechanisms on risk reporting is mediated by strategic/institutional legitimacy interests. Design/methodology/approach-From a sample of 60 non-finance Portuguese and Spanish companies with securities traded on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 74 publications
6
34
0
Order By: Relevance
“…A case in point is CBL, one of the collapsed banks, which was found to have board members without tertiary certificate, had no approved board charter and some board meetings appeared not to have taken place. Furthermore, the findings are consistent with previous studies (Agyei-Mensah and Buertey, 2019;Oliveira et al, 2018;Agyei-Mensah, 2017a;Mokhtar and Mellett, 2013) which found that some governance mechanisms significantly affect the level of RDC. The current findings confirm the significant role of BGQ in enhancing RDC of Ugandan FIs.…”
Section: 000supporting
confidence: 92%
See 3 more Smart Citations
“…A case in point is CBL, one of the collapsed banks, which was found to have board members without tertiary certificate, had no approved board charter and some board meetings appeared not to have taken place. Furthermore, the findings are consistent with previous studies (Agyei-Mensah and Buertey, 2019;Oliveira et al, 2018;Agyei-Mensah, 2017a;Mokhtar and Mellett, 2013) which found that some governance mechanisms significantly affect the level of RDC. The current findings confirm the significant role of BGQ in enhancing RDC of Ugandan FIs.…”
Section: 000supporting
confidence: 92%
“…Agyei-Mensah (2017a, b), Sellami and Fendri (2017), Juhmani (2017), Oliveira et al (2018) and Mnif and Znazen (2020), while it is inconsistent with studies of Rahman and Hamdan (2017) and Alfraih and Almutawa (2017). The findings confirm the significant role of board independence in boosting RDC in Ugandan FIs.…”
Section: Financial Institutions In Ugandamentioning
confidence: 78%
See 2 more Smart Citations
“…We measure INDAVGRC, which represents the average (mean) presence of stand-alone risk committee aligned with the peers in the same industry (two-digit SIC) during each year of the sample period (excluding the firm itself). We expect a positive association between RC and a set of corporate governance variables (BODSIZE, BODIND, BIG4), as firms with a large board size (BODSIZE), a higher number of independent directors (BODIND), and large auditors (BIG4) are more likely to set up a stand-alone risk committee (Subramaniam et al, 2009;Yatim, 2010).An audit committee is often considered as an effective monitoring mechanism to mitigate agency conflict (Oliveira et al, 2018). Therefore, we include several audit committee attributes (ACSIZE, ACINDEP, ACEXPERT) as determinants of the existing risk committee.…”
Section: Self-selection Of the Risk Committee And Corporate Risk-takingmentioning
confidence: 99%